The space of religion: temple, state, and Buddhist communities in modern China - Ashiwa, Yoshiko (The Sheng Yen Series in Chinese Buddhist Studies, 2023)
Based on three decades of ethnographic research, The Space of Religion takes readers inside the Nanputuo Temple in order to explore the practice of Buddhism in modern China and the complex relationship between Buddhism and the Chinese state.